Studies in virus diseases - Rooyen, C. E. Van (The University of Edinburgh, 1941)
In any approach to this subject it is essential first to review the relevant literature, and secondly to examine and discuss the physical, chemical and physico-chemical principles upon which instruments such as the ultra violet light, electron, and fluorescence microscopes are constructed. Only in this way can one interpret the significance of published research and correlate them with one's own deductions.

The following pages contain a comprehensive description of apparatus used, their mode of operation, scope of usefulness and methods of interpreting data. The text is subdivided into sections dealing with rnicroscopy, staining , filtration and centrifugation, in which are contained personal observations on the morphology of the elementary bodies of myxoma and their centrifugalisation, also an account of the existence of elementary bodies in Rift Valley fever.